First description of herpes simplex virus type 1 epididymo-orchitis: A new clinical form of herpes simplex virus infection during septic shock?. (2016) - Fromentin, Mélanie; Gauzit, Remy; Gille, Benoit; Samama, Charles Marc
Abstract: Genital herpes is increasingly caused by herpes simplex virus type 1 (HSV-1), but recurrences are less frequent than with HSV-2. Distinguishing between primary genital infection and reactivation can be difficult, but HSV-1 more often causes severe primary infections and fewer recurrences. However, as virus reactivation is common during septic shock, a severe form of HSV-1 reactivation can occur in locations other than the lungs, which remain the most common site. The case of a 79-year-old Caucasian man who presented with HSV-1 epididymo-orchitis after three episodes of severe sepsis or septic shock in the context of acute biliary necrotizing pancreatitis is described. This is the first reported case of HSV-1 epididymo-orchitis due to virus reactivation during sepsis.